2020
DOI: 10.1093/toxsci/kfaa055
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Exhaust Extract Exposure Induces Neuronal Toxicity by Disrupting Autophagy

Abstract: The vast majority of neurodegenerative disease cannot be attributed to genetic causes alone and as a result, there is significant interest in identifying environmental modifiers of disease risk. Epidemiological studies have supported an association between long-term exposure to air pollutants and disease risk. Here, we investigate the mechanisms by which diesel exhaust, a major component of air pollution, induces neurotoxicity. Using a zebrafish model, we found that exposure to diesel exhaust particulate extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
2
18
0
2
Order By: Relevance
“…4). This is consistent with our recent report that DEPe exposure results in lower neuronal autophagic flux and suggests a mechanism underlying neuronal toxicity of air pollution (Barnhill et al 2020).…”
Section: Phagosome Maturationsupporting
confidence: 93%
See 2 more Smart Citations
“…4). This is consistent with our recent report that DEPe exposure results in lower neuronal autophagic flux and suggests a mechanism underlying neuronal toxicity of air pollution (Barnhill et al 2020).…”
Section: Phagosome Maturationsupporting
confidence: 93%
“…The resulting embryos were dechorionated in pronase (2 mg/ ml) and treated with either DEPe (Standard Reference Materials, NIST, Gaithersburg, MD) at a final concentration of 20 μg/ml or vehicle until 5 days post-fertilization (DPF). This concentration was selected since it resulted in neuron loss as previously reported but without significant mortality (Barnhill et al 2020).…”
Section: Fish Treatment and Crispr/cas9-mediated Gene Knockdownmentioning
confidence: 99%
See 1 more Smart Citation
“…Diesel exhaust particle extracts (DEPe), commonly used as a surrogate model of air pollution in health effects studies, was used to determine the biological plausibility and mechanisms of toxicity of this association. ZF embryos treated with DEPe for 24 h (24 to 48 hpf) and analyzed at 5 dpf resulted in loss of dopaminergic as well as non-dopaminergic neurons, and altered behavior [ 97 , 98 ]. Using a transgenic ZF line that measures neuronal autophagic flux [ 99 ], it was found that DEPe inhibited flux and that the enhancers of autophagy were protective of neuronal loss.…”
Section: Toxins and The Study Of Pdmentioning
confidence: 99%
“…Autophagy, also known as "programmed cell death type Ⅱ", has become an area of focus in recent years [29][30][31] . While in most circumstances, the autophagy of the cells was maintained at low; while on the other hand, when cells were facing undesired conditions (for example, oxidative stress, heat, changes of the microenvironment etc.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%